Rancang Bangun Alat Sortir Buah Jeruk Berdasarkan Kualitas Menggunakan Mikrokontroler 8266 Berbasis IoT (Studi Kasus Toko Jeruk Nur Acil) - Reni Anggraeni; Teti Desyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of science and technology has had a positive impact on human life which has now reached modern times. There are many innovations from today's progress that continue to develop to help facilitate human work. Of the many types of innovation, most use microcontrollers in automated systems. With the addition of this Internet Of Things system, we can control and access existing electronic equipment remotely by utilizing the installed internet connection. The design of a sorting device using the esp-8266 microcontroller system control is a form of modern progress. Designing a sorting tool using a microcontroller is one way to simplify human work. The method in this study uses an experimental method that produces a sorting tool using a microcontroller with several stages of system testing starting with individual component testing, components that are connected to other components, system functional testing and system testing as a whole. The results obtained from this research are to create an automatic control system, so that the system can control electronic devices automatically or manually.